Germany et al. v. Philipp et al.: Human Rights Exception to State Immunity Rejected (Polish Yearbook of International Law, 2021)
This article discusses some recent developments in the US jurisprudence concerning state immunity. Some lower courts’ decisions handed down earlier suggested a more decisive departure from the rigid interpretation of the Foreign Sovereign Immunity Act (FSIA). If the US Supreme Court had accepted this new jurisprudential trend, it would possibly allow for carving out a partial acceptance of a human rights exception. However, the Supreme Court decided otherwise. In the recently handed-down decision in Germany et al. v. Philipp et al., the Justices rejected any innovations, unequivocally maintained the strict interpretation of FSIA Åò1603(a)(3), and by their direct reference to the International Court of Justice strengthened the existing status quo in international law as well. This note analyzes this decision’s possible consequences at the domestic and international levels. In conclusion, it seeks to place Germany vs. Philipp in a broader context. It suggests that it possibly reflects more general tendencies in the contemporary US jurisprudence, which can impact both the US domestic legal order and international law.